USM VC ATTENDS COUNCIL MEETING FOR THE PROMOTION OF EDUCATION AND RESEARCH IN TECHNOLOGY, TOKYO, JAPAN - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 28 February 2017 – Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail attended the 4th Council Meeting for the Promotion of Education and Research in Technology in Tokyo, Japan on 23 February 2017.